Pengembangan Media Pembelajaran Logic Gate Interaktif pada Mata Kuliah Elektronika Digital - Kadek Arya Prasmanta Diva; I Putu Suka Arsa; I Gede Made Surya Bumi Pracasitaram (Jurnal Pendidikan Teknik Elektro Undiksha, 2026)
Technological advancement has fundamentally reshaped the instructional demands of Digital Electronics, necessitating laboratory learning media capable of bridging theoretical comprehension with the systematic cultivation of practical competencies. Nevertheless, currently available instructional media remain predominantly confined to software-based simulations or trainer modules with fragmented functionalities, thereby limiting their effectiveness in facilitating comprehensive laboratory activities. This study sought to develop a compact trainer-based logic gate learning medium that consolidates multiple practical modules into a unified instructional platform. The investigation employed a Research and Development (R&D) methodology by adopting Sugiyono's development framework, encompassing problem identification, data collection, prototype design, expert validation, product refinement, and product implementation through field testing. The resulting trainer integrates logic gates, a signal generator, SR Flip-Flop, T Flip-Flop, a BCD decoder, a seven-segment counter, an Arduino Nano, and an LCD within a single laboratory apparatus. Validation outcomes demonstrated a feasibility rating of 96% from subject-matter experts and 80% from media experts. Product trials further revealed exceptionally favorable student perceptions, achieving approval ratings of 97% in the small-group evaluation and 95% in the large-group implementation. Collectively, these findings substantiate that the developed trainer satisfies the criteria for instructional feasibility while offering substantial potential to enhance Digital Electronics laboratory instruction through a more cohesive, efficient, and pedagogically integrated learning environment.